About the Contributors - ⠀, — (The Archive; Vol 5 No 1 (2024): Regular Issue Vol. 5, No. 1, 2024)
Jessa Aviso  is an accomplished alumna of the UP Department of Linguistics, currently serving as a project coordinator in the technology industry. With experience in diverse projects, she has honed her language and communication skills. She is passionate about innovative technologies and their impact on language, believing they can enrich and evolve communication in our society. Brian Salvador Caratao Baran  is currently an Instructor at the UP Department of Linguistics. His research interests include Bisayan languages, Japonic languages, language description, dialectology and variation, and particles. Cheska Cendaña is an alumna of the UP Department of Linguistics and currently a medical student at Mariano Marcos State University College of Medicine. Her research interests span across linguistics and medicine, with a particular focus on historical linguistics and the use of language in healthcare contexts. Through her interdisciplinary work, she aims to contribute to a better understanding of how language impacts patient care and healthcare accessibility. Si Anicia del Corro  ay isang expert sa larangan ng Linguistics at Theology. Natapos niya ang kanyang Bachelor of Arts, Master of Arts, at Doctor of Philosophy na lahat major sa Linguistics sa University of the Philippines Diliman. Bukod dito, nagtapos din siya ng Master of Theology sa Union Theological Seminary sa Virginia, USA. Siya ang translation consultant sa unang natapos na Heterogeneous Language translation ng Bible para sa New Testament at Psalms and Proverbs mula 2007 hanggang 2021. Ipinublish ang buong Bible noong 2023 ng Philippine Bible Society, Inc. Julia Magno  is an alumna of the UP Department of Linguistics, which has also published her undergraduate capstone research about the Messenger reacji. Also a singer-songwriter and yodeler known as \blockquote{gossamery}, she has written and translated songs in several languages and has performed at international events, including the SOAS GLOCAL Conference on Asian Linguistic Anthropology in 2023. She is currently a sophomore at the UP College of Law. Briar Rose Tan  is a graduate of the Department of Linguistics at the University of the Philippines Diliman. Her academic research interests include social media slang and Tagalog discourse particles. She is currently a content researcher and scriptwriter for an international brand.